Plasma Aβ42/Aβ40 and p-tau181 Predict Long-Term Clinical Progression in a Cohort with Amnestic Mild Cognitive Impairment. (8th October 2022) - Xiao, Zhenxu; Wu, Wanqing; Ma, Xiaoxi; Liang, Xiaoniu; Lu, Jiaying; Zheng, Li; Ding, Saineng; Lei, Qiqi; Luo, Jianfeng; Chen, Keliang; Ding, Ding; Zhao, Qianhua
Abstract: Background: Previous studies reported the value of blood-based biomarkers in predicting Alzheimer disease (AD) progression among individuals with different disease stages. However, evidence regarding the value of these markers in those with amnestic mild cognitive impairment (aMCI) is insufficient. Methods: A cohort with 251 aMCI individuals were followed for up to 8 years. Baseline blood biomarkers were measured on a single-molecule array platform. Multipoint clinical diagnosis and domain-specific cognitive functions were assessed to investigate the longitudinal relationship between blood biomarkers and clinical AD progression. Results: Individuals with low Aβ42/Aβ40 and high p-tau181 at baseline demonstrated the highest AD risk (hazard ratio = 4.83, 95% CI 2.37–9.86), and the most dramatic decline across cognitive domains. Aβ42/Aβ40 and p-tau181, combined with basic characteristics performed the best in predicting AD conversion (AUC = 0.825, 95% CI 0.771–0.878). Conclusions: Combining Aβ42/Aβ40 and p-tau181 may be a feasible indicator for AD progression in clinical practice, and a potential composite marker in clinical trials.